The problematic nature of steel hollow section joint fabrication, and a remedy using laser cutting technology: A review of research, applications, opportunities. (15th March 2019) - Kanyilmaz, Alper
Highlights: CHS joints are manufactured with a vast amount of welds and local stiffeners. This may result in high fabrication costs and low structural reliability. Laser cutting technology can enable a simplified fabrication of CHS joints. This would bring substantial savings to the steel fabrication costs and waste. The paper presents a comprehensive literature review on this topic. Abstract: In steel buildings, circular hollow sections (CHS) present several advantages such as uniform behaviour in all directions, the possibility of obtaining composite behaviour by concrete infill, hence high strength, stability and good fire resistance. Moreover, their aesthetic appeal has great potential for influencing the choice of the decision makers (architect, building owner). However, CHS profiles are not widely adopted in current practice due to the complexity and high cost of their joint details. Their joints are manufactured with a vast amount of welds and local stiffeners, which results in high fabrication costs and energy consumption, and low structural reliability under extreme loads. As a possible remedy to the complex hollow section joint fabrication, this article highlights the opportunities provided by the laser cutting technology (LCT). LCT, unleashed from the constraints of traditional cutting techniques (such as large heat-affected zones, high maintenance need, slow-to-moderate speed, low precision and low cut-edge quality) can enable a simplified fabrication of hollow section joints, bringing substantial savings to the steel fabrication costs and material waste. This paper summarizes the problems in the joint fabrication of tubular structures, and presents a comprehensive literature review containing design guidelines regarding hollow section joints, use of different materials (high strength steel, stainless steel), and configurations (external diaphragm, steel-concrete composite, passing through, truss joints). It presents the LCT process parameters in relation with different steels (carbon, high strength, stainless steel), structural integrity of laser-cut profiles (issues related to heat-affected zone, static and fatigue properties, effect of surface conditions, cut geometry and welding), available structural cutting possibilities (for bolt holes, beam perforations, open and hollow section profiles), cut tolerances as well as their effect on welding, and LCT's cost and environmental impact. Finally, the current outcomes of an ongoing European research project have been presented which study the hollow section joint fabrication making use of LCT.